Exposure of metal toxicity in Alzheimer’s disease: An extensive review - Islam, Fahadul; Shohag, Sheikh; Akhter, Shomaya; Islam, Md. Rezaul; Sultana, Sharifa; Mitra, Saikat; Chandran, Deepak; Khandaker, Mayeen Uddin; Ashraf, Ghulam Md; Idris, Abubakr M.; Emran, Talha Bin; Cavalu, Simona (Frontiers in Pharmacology, 2022)
Metals serve important roles in the human body, including the maintenance of cell structure and the regulation of gene expression, the antioxidant response, and neurotransmission. High metal uptake in the nervous system is harmful because it can cause oxidative stress, disrupt mitochondrial function, and impair the activity of various enzymes. Metal accumulation can cause lifelong deterioration, including severe neurological problems. There is a strong association between accidental metal exposure and various neurodegenerative disorders, including Alzheimer's disease (AD), the most common form of dementia that causes degeneration in the aged. Chronic exposure to various metals is a well-known environmental risk factor that has become more widespread due to the rapid pace at which human activities are releasing large amounts of metals into the environment. Consequently, humans are exposed to both biometals and heavy metals, affecting metal homeostasis at molecular and biological levels. This review highlights how these metals affect brain physiology and immunity and their roles in creating harmful proteins such as β-amyloid and tau in AD. In addition, we address findings that confirm the disruption of immune-related pathways as a significant toxicity mechanism through which metals may contribute to AD.